Assessment of debonding in gfrp joints using damage identification techniques - Chryssanthopoulos, Marios K.; Votsis, Renos (My University, 2009)
Pultruded sections are used in many different civil engineering applications involving FRP composites, including a number of footbridges. These sections are typically joined through adhesive bonding and/or mechanical interlock. The joint is clearly critical to load transfer and the avoidance of unintended failure modes. As a contribution towards studying damage identification and assessment in FRP joints, this paper examines the dynamic performance of bonded GFRP pultruded sections. Experimental testing and FE modelling were employed to model damage in the joints and to assess whether debonding can be detected through differences in the dynamic characteristics - namely frequencies and mode shapes - of the components. Debonding in the joints was simulated by progressively reducing their bonded area. Four damage identification techniques (based on modal curvature, flexibility, damage index and the curvature of the flexibility-based uniform load surface) were used to assess damage. The results show that significant damage has to be present before debonding can be identified through changes in resonant frequencies and mode shapes. Once such levels are present, damage identification techniques can be applied effectively to locate damage. It is concluded that vibration-based damage assessment methods should be used in conjunction with other non-destructive evaluation techniques.
Keywords: GFRP joints; Vibration testing; Damage assessment; Pultruded sections